The Video encyclopedia of physics demonstrations - Education Group & Associates (Los Angeles, CA : the Education Group & Associates, 1992)
A videodisc survy of physics demonstrations.
Disc 1. Units and vectors, linear kinematics, linear dynamics -- Disc 2. Motion in a plane, inertia, action and reaction -- Disc 3. Friction, work, energy and power, center of mass -- Disc 4. Statics -- Disc 5. Collisions, rotational kinematics -- Disc 6. Rotational acceleration and energy -- Disc 7. Conservation of angular momentum, precession, rotational phenomena, gravitation -- Disc 8. Elasticity, ocillations -- Disc 9. Resonance, mechanical waves, standing waves -- Disc 10. Sound production, properties of sound -- Disc 11. Standing sound waves, gas pressure -- Disc 12. Fluid pressure, buoyancy -- Disc 13. Fluid dynamics, surface tension -- Disc 14. Viscosity, thermal phenemona, heat transfer -- Disc 15. Laws of thermodynamics, phase changes -- Disc 16. Kenetic theory, crystals and low temperatures, thermoelectrity, electric charges -- Disc 17. Elecrostatic induction, electric fields, resistance and DC circuits -- Disc 18. Voltage drops and 1 p2 sR losses, Non-ohmic resistance, electrochemical effects, capacitance and RC circuits -- Disc 19. Magnetism and magnetic fields, magnetic fields from currents.
Title from container.
CAV standard-play.
Keywords: Physics -- Experiments; Physics